Faktor-Faktor Yang Berpengaruh Pada Akuntabilitas Pengelolaan Dana Desa - Dewi, Ni Komang Ayu Julia Praba; Gayatri, Gayatri (E-Jurnal Akuntansi, 2019)
This study aims to obtain empirical evidence of the influence of competence, leadership, and participation in accountability of village fund management. This study was conducted on 14 village in Abang District, Karangasem Regency. Respondents in this study were 140 people who were determined using a non-probability sampling, namely purposive sampling. Data collected by questionnaire method. Data analysis technique used in this study is multiple linear regression test. The result of the study showed that competency, leadership, and participation had a positive effect on the accountability of village fund management. Keywords : Accountabilitty, competence, leadership, participation.